2011
DOI: 10.1016/j.brainres.2011.02.074
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of downstream MyD88 or TRIF Toll-like receptor signaling does not protect against cerebral ischemia

Abstract: Toll-like receptor (TLR) signaling plays an important role in cerebral ischemia, but downstream signaling events, which can be organ-specific, are incompletely understood. We thereby investigated involvement of the MyD88-dependent (MyD88) and MyD88-independent (TRIF) TLR signaling pathways in 2 in vitro and 2 in vivo models of cerebral ischemia. For in vitro studies, we used a model of oxygen-glucose deprivation (OGD) followed by flow cytometric analysis to determine:1) viability of PC12 cells following knock-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 24 publications
2
28
1
Order By: Relevance
“…However, our previous studies showed similar expression of MyD88-mediated cytokines in TRIF-mutant and WT mice, 11 but mice with disruption of TRIF were not protected against focal cerebral ischemia. 12 We postulate that the baseline cytokine changes, reported in our previous study, 11 were limited to the MyD88 versus WT comparison, in part, because immediate early genes, such as EGR1, which was increased at baseline in MyD88 À / À and TRIF-mutant mice, compared to WT mice, in our current study, are known to affect the expression of MyD88-specific cytokines, such as IL-6. 28,29 Taken together, these previous results of a cytokine profile similar to WT mice, and the current additional role for TRIF in ischemia-mediated immediate early gene expression, suggest that both optimal cytokine and immediate early gene expression might be essential for the optimal acute phase response to focal cerebral ischemia.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…However, our previous studies showed similar expression of MyD88-mediated cytokines in TRIF-mutant and WT mice, 11 but mice with disruption of TRIF were not protected against focal cerebral ischemia. 12 We postulate that the baseline cytokine changes, reported in our previous study, 11 were limited to the MyD88 versus WT comparison, in part, because immediate early genes, such as EGR1, which was increased at baseline in MyD88 À / À and TRIF-mutant mice, compared to WT mice, in our current study, are known to affect the expression of MyD88-specific cytokines, such as IL-6. 28,29 Taken together, these previous results of a cytokine profile similar to WT mice, and the current additional role for TRIF in ischemia-mediated immediate early gene expression, suggest that both optimal cytokine and immediate early gene expression might be essential for the optimal acute phase response to focal cerebral ischemia.…”
Section: Discussionmentioning
confidence: 61%
“…26 However, disruption of MyD88 signaling does not protect against focal cerebral ischemia, in in vitro and in vivo models. 12 Surprisingly, this lack of protection occurs in spite of decreased levels of proinflammatory cytokines in the serum and brains of MyD88 À / À mice following focal cerebral ischemia. 11 To date, a molecular basis for these confounding results has not been known.…”
Section: Discussionmentioning
confidence: 99%
“…However, in an experiment using TLR2-or TLR4-deficient mice with wild-type BM, no improvement was observed in ischemic brain injury (Yang et al 2011;Shichita et al 2012). Moreover, mice lacking MyD88, the adaptor protein required for almost all TLR signaling cascades (other than TLR3), showed either no improvement or exaggeration of ischemic brain injury (Famakin et al 2011). These results indicate that the function of TLRs is dependent of the cell types in the brain and the timing of their activation.…”
Section: Tlrs As Damps Receptorsmentioning
confidence: 68%
“…However, Famakin et al illustrated that the elimination of neither MyD88 adaptor nor TRIF does protect against ischemia. They performed the experiments in OGD cell culture and PC12 cell viability as two in vitro models and two in vivo models of permanent middle cerebral artery occlusion and global cerebral ischemia (Famakin et al, 2011). The investigation did not point to a significant difference among groups.…”
Section: Tlrs and Neurodegenerationmentioning
confidence: 99%